Answer:
Option (2)
Explanation:
To get the transformation applied in triangle ABC to map triangle DEF we will apply the following rules.
If a point A of triangle ABC maps the point D of triangle DEF,
Coordinates of point A → (-4, -5)
Coordinates of point D → (2, 6)
First point A is shifted to quadrant (4) from quadrant (3),
Rule for the translation,
A(x, y) → A'(x + 6, y - 1)
A(-4, -5) → A'(2, -6)
Followed by reflection across x-axis (y = 0)
A'(x, y) → D(x, -y)
A'(2, -6) → D(2, 6)
Therefore, Option (2) will be the answer.